COMPARATIVE ANALYSIS OF FINANCIAL PERFORMANCE FOR BANKING COMPANIES BASED ON BUKU I AND BUKU IV - Panjaitan, Raya; Simbolon, Ika Pratiwi (Sekolah Tinggi Ilmu Ekonomi Sultan Agung Pematangsiantar, 2024)
The research aim is to test the difference between bank performance as measured by ROA and NIM for BUKU I and BUKU IV Banks in Indonesia. The paper uses monthly data from annual report. There is significant difference between bank performance for BUKU I and BUKU IV. Policy makers, investors and other shareholders should consider the results of this study in making important policies. The performance of banks is quite different if they have different amounts of capital. Regarding the research limitations, future research can use the research object not limited to comparative analysis of banking companies, but more to discover research model for bank performance determinants for each bank categories based on capital. Future research may use longer period for better prediction ability.